Effects of short- and long-term exposure to cadmium on salivary glands and fat body of soil centipede Lithobius forficatus (Myriapoda, Chilopoda): Histology and ultrastructure. (October 2020) - Rost-Roszkowska, Magdalena; Poprawa, Izabela; Chajec, Łukasz; Chachulska-Żymełka, Alina; Leśniewska, Małgorzata; Student, Sebastian
Highlights: Alterations in the salivary glands and fat body at the ultrastcrtural level have been caused by cadmium short- and long-term exposure. Changes connected with cell death (autophagy, apoptosis, necrosis), and the crosstalk between them, occurred. Different organs in the body can react differently to the same stressor, as well as to the same concentration and time of exposure. Abstract: Cadmium (Cd) is the most widely studied heavy metal in terms of food-chain accumulation and contamination because it can strongly affect all environments (e.g., soil, water, air). It can accumulate in different tissues and organs and can affect the organism at different levels of organization: from organs, tissues and cells though cell organelles and structures to activation of mechanisms of survival and cell death. In soil-dwelling organisms heavy metals gather in all tissues with accumulation properties: midgut, salivary glands, fat body. The aim of this study was to describe the effects of cadmium on the soil species Lithobius forficatus, mainly on two organs responsible for gathering different substances, the fat body and salivary glands, at the ultrastructural level. Changes caused by cadmium short- and long-term intoxication, connected with cell death (autophagy, apoptosis, necrosis), and the crosstalk between them, were analyzed. Adult specimens of L. forficatus were collected in a natural environment and divided into three experimental groups: C (the control group), Cd1 (cultured in soil with 80 mg/kg of CdCl2 for 12 days) and Cd2 (cultured in soil with 80 mg/kg of CdCl2 for 45 days). Transmission electron microscopy revealed ultrastructural alterations in both of the organs analyzed (reduction in the amount of reserve material, the appearance of vacuoles, etc.). Qualitative analysis using TUNEL assay revealed distinct crosstalk between autophagy and necrosis in the fat body adipocytes, while crosstalk between autophagy, apoptosis and necrosis in the salivary glands was detected in salivary glands of the centipedes examined here. We conclude that different organs in the body can react differently to the same stressor, as well as to the same concentration and time of exposure. Different mechanisms at the ultrastructural level activate different types of cell death and with different dynamics.